Development of Canva Based E-Module to Foster Multiliteracy in Fraction Material - Sayyidatul Karimah; Rini Utami; Erwan Kustriyono; Ahmad Aunur Rohman (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
This research aims to develop learning media in the form of a Canva-based e-module on fraction material to foster students' multiliteracies. This type of research is a development research with the Plomp development model. In this model, the stages carried out are: (1) the initial investigation stage, (2) the design stage, (3) the realization/construction stage, (4) the test, evaluation and revision stage). The instrument used in this study was a questionnaire sheet in the form of a validation questionnaire to measure the validity of the product developed and a response questionnaire to measure the practicality of the product developed as well as a test to determine the effectiveness of the product developed. The results of the study showed that the learning media in the form of a Canva-based e-module on fraction material to foster multiliteracies was valid with a validation value of 3.86 and practical with a response questionnaire value of 91%. The results of the pretest and posttest showed an increase of 0.72 (high criteria). Based on these results, it can be concluded that the Canva-based e-module is valid, practical and effective so that it can be used by teachers and students in mathematics learning. Keywords: Canva, E-Module, Fraction, Multiliteracy